PROFIL KEMAMPUAN LITERASI STATISTIS MAHASISWA JURUSAN PENDIDIKAN MATEMATIKA UNIVERSITAS SULTAN AGENG TIRTAYASA - Etika Khaerunnisa; Aan Subhan Pamungkas (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
ABSTRACTAs an effort to achieve meaningfulness in the research process conducted by students, it requires a student ability covering ability compile to with refer to the question to be researched, formulating statistical hypothesis, solving, and interpreting problems which is relied by existing context, this ability is known as statistical literacy. The purpose of this study is to describe and assess the ability of statistical literacy. By knowing the ability of statistical literacy early on in the first semester, it will be able to be developed furthermore realization of subject circumstances under study in further statistics. The method used in this research is qualitative method with type of research strategy of case study. The subjects of the study are students majoring in mathematics education semester I in the basic statistics courses of the academic year 2016/2017. Research instrument that is researcher as main instrument, and statistic literacy test. The result of the research is 35% of students are in the high statistic literacy ability category, 13% of students are in the medium category, and 52% of students are in the low category, with different achievement in each capability category viewed from three indicators of statistical literacy ability. They are Formulating problems ability; Using concepts ability, facts, procedures and reasoning; Interpreting problems solving ability. Keywords: Statistical literacy ability, student of mathematics education